Implementation Of Counterterrorism In Eradication Of Terrorism Criminal Acts In Indonesian Positive Law Legislation - Rahman, Abdul; Huda, Misbahul (LITERATUS, 2024)
Through counterterrorism policies, the government can mobilize various public work sectors which ultimately improve the quality of security and welfare provisions by the state. Improving the handling of terrorism convicts in prison to prevent recidivism, for example, will improve the detention system, immigration system and civil registration. This is of course with an important note that the policy of responding to terrorism is carried out in a coordinated manner. So, not only certain institutions within the country, but all state institutions must have a clear role in responding to terrorism. The formulation of the problem discussed is: How can counterterrorism efforts prevent and overcome terrorism? and How is counter-terrorism implemented in eradicating criminal acts of terrorism into Indonesian positive law legislation? The research method used in this research is normative juridical research with a statutory approach and a conceptual approach. Discussion: The application of counter-terrorism in eradicating criminal acts of terrorism in Indonesia has been integrated into positive legal legislation through Law no. 5 of 2018. This law strengthens the legal framework by expanding the definition of terrorism, tightening supervision, and giving greater authority to security forces, as well as introducing preventive measures such as preventive detention and deradicalization. The role of the National Counter-Terrorism Agency (BNPT) has also been strengthened to coordinate counter-terrorism strategies. The legislative process in Indonesia which follows the civil law tradition requires regulations to be written in writing. Establishment of Law no. 5 of 2018 was also influenced by the phenomenon of acts of terrorism which prompted the acceleration of the revision of Law no. 15 of 2003. Encouragement from society (bottom-up) and responses from political actors accelerated the ratification of this law, even though there were various challenges related to expanding authority and human rights. In dealing with terrorism, Indonesia applies two main approaches, namely the criminal justice model and the war model. The criminal justice model views terrorism as a legal violation that is handled through law enforcement, while the war model views it as an existential threat that requires a military response.